Knowledge, Attitude and Practice of Medical Students of Sulaimani Regarding Modern Lifestyle and Its Effect on Health - M. Ali, Bushra; Mohammed, Saman; Akram, Shajwan; Salar, Saya; Baxtiar, Lezan; Ismail, Lawen; Nawzad, Shad (Kurdistan Journal of Applied Research, 2020)
The objectives of this study are to assess level of knowledge, attitude and practice of medical students about modern lifestyle and its impact upon health, in association with different colleges. A cross sectional study was conducted among 420 students, in a convenient sampling way, Data collected from 18th to 22nd of September 2019 in a self-administrated manner from four different medical colleges (Medicine, Dentistry, Pharmacy and Veterinary.) in university of Sulaimani. Data entered on Excel sheets and analyzed with SPSS program version 22. Chi square was used to get the association P value equal and less than (0.05) regarded statistically significant. Most of the students (82.1%) had heard about a modern lifestyle with highest percentage of participants (90.5%) from college of medicine, and (69.3%) knew that technology has a major role in creating a modern lifestyle, with a significant P value of (0.001). Nearly half of the students (54.5%) believed to be living a modern lifestyle and most of them (66.2%) were from college of dentistry. About (49.5%) of students believed that financial status can sometimes put limits on lifestyle choice with most of them (52.7%) being from college of dentistry with p value of (0.001). Majority of students (995%) used social media with most of them (97.4%) being from college of medicine. Nearly (66%) of participants didn’t exercise and highest percentage (78.1%) from college of pharmacy with a significant (P value 0.007). Participants in general had good knowledge and positive attitude regarding the topic, but they had a negative practice with managing stress, time and depression and had negative habits regarding exercise and having healthy diet. In addition college of medicine had highest knowledge and attitude among the four medical colleges, but regarding the practice college of pharmacy was the best.